THE HISTORY OF THE STUDY OF CULTURAL HERITAGE SITES IN THE SURKHAN OASIS REGIONS (American Journal of Research in Humanities and Social Sciences, 2026)
This article explores the historical significance and study of cultural heritage sites located in the Surkhan oasis. Using examples such as Dalverzintepa, Fayoztepa, the Mausoleum of Hakim at-Termezi, and the Boysun traditions, it analyzes the region’s tangible and intangible heritage. The paper highlights research stages from the 19th century to the present, including Soviet-era excavations and UNESCO-supported restoration projects in the independence period. It also outlines future prospects for preserving and promoting the Surkhan oasis’s cultural heritage for upcoming generations.